184k views
5 votes
(3n³ - 5n + n²) - (-8n² + 3n³) please shawty please

User Manu
by
5.0k points

2 Answers

4 votes

Answer:


9n^2 - 5n

Explanation:


(3n^3 - 5n + n^2) - (-8n^2 + 3n^3)

Lets open the brackets. Signs of all the terms in the bracket next to the minus sign will change.


=> 3n^3 - 5n + n^2 + 8n^2 - 3n^3

Now lets add/substract all the like terms with each other.


=> 3n^3 - 3n^3 + n^2 + 8n^2 - 5n


=> 9n^2 - 5n \: \: or \:\: n(9n - 5)

User Cosinus
by
5.1k points
4 votes

Answer:

Explanation:


3n^3-5n+n^2+8n^2-3n^3\\ \\ 9n^2-5n\\ \\ or\ n(9n-5)

User Tung
by
4.8k points